al- Imtāʾ bi-sīrat al-imāmain al-Ḥasan Ibn-Ziyād wa-ṣāḥibihi Muḥammad Ibn-Šuǧāʿ - Kauṯarī, Muḥammad Zāhid al- 1879-1952 (Min turāṯ al-Kauṯarī, 2003)
Luʼluʼī, al-Ḥasan ibn Ziyād d. 819 or 20; Ibn al-Thaljī, Muḥammad ibn Shujāʻ, 797 or 8-879 or 80; Muslim scholars; Hanafites; biographies